Environmental change and migration in coastal regions: examples from Ghana and Indonesia - Hillmann, Felicitas; Ziegelmayer, Usha (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
Coastal regions worldwide have been focal points for migration as well as affected by environmental changes for a long time. In the debate on climate change and migration coastal regions are among the “hot spot” areas that are supposed to be prone to “climate migration” in the near future. The paper analyses the situation in two different regional settings and advocates for a sound regional perspective on the relationship of environmental change and migration. Based on the conceptual framework of migrant trajectories, the paper shows how populations in Keta (Ghana) and Semarang (Indonesia), affected by similar environmental changes such as flooding and erosion, react quite differently in terms of migration and mobility. The regional perspective as well as each region’s past experiences with migration and environmental changes shows to be crucial in order to understand current reactions to environmental degradation. The Keta setting represents a typology that pronounces migration trajectories as part of long-standing interregional and international migration, the Semarang setting, however, may be classified as a rather typical modernization-induced migration scheme, linked to rapidly growing urbanisation, with “trapped populations” on the one hand and in-migration of migrant workers on the other hand.